Pengaruh Pemberian Variasi Gula Pasir Pada Minuman Daun Pegagan (Centella asiatica (L.) Urban) Terhadap Organoleptik dan Kadar β-Karoten - Vitri Agustiarini; Fauziyah Fauziyah; Dina Permata Wijaya (Jurnal Penelitian Sains, 2020)
Pegagan (Centella asiatica (L.) Urban) is a plant that contains compounds that can protect the body from free radicals. Pegagan leaves contain β-carotene. The purpose of this study was to determine the effect of giving variations of sugar in the drink Pegagan (Centella asiatica (L.) Urban) on organoleptic and β-carotene levelsThis study used an experimental method using a completely randomized design (CRD) with two factors, factor 1, namely the weight of pegagan leaves (P1 = 50 grams and P2 = 70 grams) and factor 2, namely sugar (G1 = 50 grams, and G2 = 100 grams). ) with 4 treatments and 2 repetitions. The results showed that the weight of pegagan leaves and sugar had an effect on the β-carotene content of pegagan leaf drink. The highest β-carotene content of pegagan leaf drink was treated with 70 grams of pegagan leaves and 100 grams of sugar (P2G2) which was 540.60 μg. The lowest β-carotene content of pegagan leaf drink in the treatment of pegagan leaves was 50 grams and sugar 50 grams (P1G1) was 216.97 μg. The organoleptic results of pegagan leaf drink were green, had a less distinctive aroma and pegagan leaf drink which was most preferred by panelists in the treatment of P1G1 (50 grams of pegagan leaves and 50 grams of sugar), P1G2 (50 grams of pegagan leaves and 100 grams of sugar) and P2G2 (leaves pegagan 70 grams and 100 grams of sugar).Keywords: pegagan, β-carotene, organoleptic